Extrusion-molded body

By combining vinyl copolymers with specific molecular weight distribution with catalysts, vinyl copolymers with excellent moldability and mechanical properties are prepared, which solves the problem of insufficient moldability and wear resistance of ultra-high molecular weight polyethylene, and achieves the improvement of high dispersion and environmental durability.

JP2025017871APending Publication Date: 2025-02-06TOSOH CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023121185
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

The prior art is difficult to improve the environmental durability and wear resistance of ultra-high molecular weight polyethylene while maintaining good moldability and mechanical strength, and its molding processability has limitations.

Method used

Using a vinyl copolymer with a specific molecular weight distribution, a vinyl copolymer with excellent moldability and mechanical properties is prepared by combining a vinyl copolymer with a dual-mode molecular weight distribution with a specific catalyst. The combination of a specific catalyst and a vinyl copolymer is achieved to achieve high dispersion and improved mechanical properties.

Benefits of technology

It realizes the high dispersion and excellent moldability and mechanical properties of vinyl copolymers, improves the wear resistance and environmental durability of the molded body, and is suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025017871000001
    Figure 2025017871000001
  • Figure 2025017871000002
    Figure 2025017871000002
  • Figure 2025017871000003
    Figure 2025017871000003
Patent Text Reader

Abstract

To provide an extrusion-molded body that excels in impact resistance, environmental load resistance, and abrasion resistance, thanks to its polyethylene composition of polyethylene and high-molecular-weight ethylene-based resin with a bimodal molecular weight.SOLUTION: There is provided an extrusion-molded body made of a polyethylene composition comprising: an ethylene-based resin having an HLMFR of 0.01 to 100 g / 10 min at a temperature of 190°C and a load of 21.6 kg, and a bimodal elution curve as measured by GPC; and polyethylene having an MFR of 0.01 to 10 g / 10 min at a temperature of 190°C and a load of 2.16 kg and a density of 930 to 980 kg / m3.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a specific extrusion molded product, and more specifically, to an extrusion molded product that has excellent extrusion moldability, impact resistance, environmental load resistance, and abrasion resistance, and is expected to have a thinner wall and a longer life as a molded product. [Background technology]

[0002] Polyethylene is a resin used in a wide range of applications, and in order to make it suitable for each application, technologies have been proposed to control the molecular weight distribution and composition by combining two or more resin components, thereby improving various physical properties and appearance. For example, an increase in higher molecular weight components improves mechanical strength but decreases moldability, while an increase in lower molecular weight components decreases mechanical strength but improves moldability.

[0003] As a method for combining two or more types of polyethylene components, there have been proposed a method in which each component is polymerized and then blended by melt kneading or dry blending, a method in which multi-stage polymerization is carried out continuously, a method in which two or more types of polyethylene components are simultaneously produced by adding a plurality of transition metal catalysts to a polymerization system, a method in which a combination of these is carried out, etc. In addition, a resin modifier has also been proposed (see, for example, Patent Document 1) that is blended with a target material to modify the physical properties, appearance, etc. of the target material.

[0004] In the drawing, spinning, blow molding, injection molding, inflation molding, and extrusion molding of polyethylene, materials with good moldability and physical properties are generally required. In recent years, there has been a demand for lighter weight and thinner walls to reduce costs, but at the same time, there is a demand for excellent mechanical strength.

[0005] Ultra-high molecular weight polyethylene, which has attracted attention in recent years (see, for example, Patent Documents 2 and 3), has an extremely high molecular weight equivalent to a viscosity average molecular weight (hereinafter sometimes referred to as Mv) of 1 million or more, and therefore has excellent impact resistance, self-lubrication, abrasion resistance, weather resistance, chemical resistance, dimensional stability, etc., and has high physical properties comparable to those of engineering plastics. For this reason, attempts have been made to apply it to uses such as sheets, films, high-strength fibers, sliding members, lining materials, line parts in the food industry, machine parts, artificial joints, sporting goods, microporous membranes, and separators by various molding methods.

[0006] However, because of its high molecular weight, ultra-high molecular weight polyethylene has extremely low fluidity when melted, and it is difficult to mold it by kneading and extrusion like ordinary polyethylene, which has a molecular weight in the range of several tens of thousands to about 300,000.Therefore, ultra-high molecular weight polyethylene is molded by various methods, such as direct sintering of the polymer powder obtained by polymerization, compression molding, molding using a ram extruder in which extrusion molding is performed while intermittently compressing, and extrusion molding into a sheet, film, or fiber shape in a state where it is uniformly mixed with a plasticizer, and in some cases, stretching it and then removing the solvent.

[0007] In order to improve the moldability of ultra-high molecular weight polyethylene and its mixability with other resins, a method of adding low molecular weight polyethylene has been proposed (see, for example, Patent Documents 4 and 5), and an ultra-high molecular weight polyethylene exhibiting a specific melting behavior has been proposed (see, for example, Patent Document 6). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2017-179304 A [Patent Document 2] Patent No. 4868853 [Patent Document 3] Patent No. 6405888 [Patent Document 4] Patent No. 4173444 [Patent Document 5] Patent No. 7071966 [Patent Document 6] JP 2021-172716 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, although the modified material proposed in Patent Document 1 was effective in improving processability to a certain extent, further improvement was required in terms of improving mechanical strength.

[0010] Moreover, Patent Documents 2 and 3 merely propose ultra-high molecular weight polyethylene, and have problems with moldability. The proposals in Patent Documents 4 to 6 also only improve the processability of ultra-high molecular weight polyethylene, and still have problems with versatility.

[0011] Therefore, there has been a demand for the development of extrusion molded articles that are excellent in mechanical properties, environmental load resistance, and abrasion resistance without impairing the processability, particularly extrusion moldability, of general-purpose resins. [Means for solving the problem]

[0012] Means for Solving the Problems The present inventors have conducted intensive studies to solve the above problems and have found that a polyethylene composition of an ethylene-based resin and a polyethylene having specific melting properties and molecular weight configuration has excellent extrusion moldability and can give an extrusion molded article having excellent impact resistance, environmental load resistance and abrasion resistance, thereby completing the present invention.

[0013] That is, the present invention relates to: (1) an ethylene-based resin having a high melt flow rate (HLMFR) of 0.01 to 100 g / 10 min at a temperature of 190° C. and a load of 21.6 kg in accordance with JIS 6922-2:1997 and a bimodal elution curve measured by gel permeation chromatography; and (2) an ethylene-based resin having a melt flow rate (MFR) of 0.01 to 10 g / 10 min at a temperature of 190° C. and a load of 2.16 kg in accordance with JIS 6922-2:1997 and a density of 930 to 980 kg / m as measured according to JIS K6922-1 (1997). 3 The present invention relates to an extrusion molded article characterized in that it is made of a polyethylene composition containing a polyethylene of the formula:

[0014] The present invention will be described in detail below.

[0015] The extrusion molded product of the present invention comprises: (1) an ethylene-based resin (C) having a melt flow rate (hereinafter sometimes referred to as HLMFR) of 0.01 to 100 g / 10 min at a temperature of 190° C. under a load of 21.6 kg in accordance with JIS 6922-2:1997 and a bimodal elution curve measured by gel permeation chromatography (hereinafter sometimes referred to as GPC); and (D) an ethylene-based resin (E) having a melt flow rate (hereinafter sometimes referred to as MFR) of 0.01 to 10 g / 10 min at a temperature of 190° C. under a load of 2.16 kg in accordance with JIS 6922-2:1997 and a density of 930 to 980 kg / m3 measured according to JIS K6922-1 (1997). 3The polyethylene composition (e) containing polyethylene (d) is an extrusion molding, and the ethylene-based resin (c) may be a bimodal ethylene-based resin having a relatively high molecular weight that exhibits melting behavior and a bimodal elution curve measured by GPC that exhibits two peaks, and examples thereof include ethylene homopolymers and ethylene-α-olefin copolymers, and examples of the α-olefins in this case include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, etc., and it is preferable that the extrusion molding is an ethylene homopolymer, since it is particularly excellent in impact resistance and abrasion resistance. Similarly, examples of the polyethylene (d) include ethylene homopolymers and ethylene-α-olefin copolymers, and examples of the α-olefins in this case include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, etc., and it is preferable that the extrusion molding is an ethylene homopolymer, since it is particularly excellent in impact resistance and abrasion resistance.

[0016] The ethylene-based resin (iii) has (1) an HLMFR of 0.01 to 100 g / 10 min and exhibits melt fluidity. If it is less than 0.01 g / 10 min, the melt fluidity is poor and the processability when forming an extrusion molded article is poor. On the other hand, if it is more than 100 g / 10 min, the mechanical properties of the extrusion molded article are poor.

[0017] The ethylene resin (iii) constituting the extrusion molded article of the present invention is an ethylene polymer having a bimodal molecular weight distribution, and preferably contains a specific ultra-high molecular weight polyethylene component (i) as a specific component, since it results in an extrusion molded article having an excellent balance between processability and mechanical properties. In this case, the bimodal molecular weight distribution is preferably one in which the elution curve measured by GPC has two peaks, and when the elution curve is expressed as a differential molecular weight distribution (x-axis: Log[M], y-axis: differential distribution value) and the peaks are divided into two normal distributions (normal distribution of the ultra-high molecular weight polyethylene component (i) and normal distribution of the polyethylene component (ii)) according to the following formula (i), it satisfies (2-1) to (2-3). f(x)=a×(1 / (2π(σ 2 ))(1 / 2) ) exp(-((x-μ) 2 ) / (2(σ 2 ))) Formula (i) (Here, a is the peak intensity, σ is the standard deviation, x is the variable, and μ is the mean.) (2-1) The ultra-high molecular weight polyethylene component (a) (hereinafter may be referred to as component (a)) represented as a high molecular weight peak component has a weight average molecular weight (hereinafter may be referred to as Mw) of 900,000 to 5,000,000 and a molecular weight distribution expressed as Mw / number average molecular weight (hereinafter may be referred to as Mn) of 2.0 to 5.0, (2-2) The polyethylene component (b) (hereinafter may be referred to as component (b)) represented as a low molecular weight peak component has an Mw of 10,000 to 500,000 and an Mw / Mn of 2.0 to 5.0, and (2-3) the component (a) / component (b) (weight ratio) is greater than 5 / 95 and less than 80 / 20, and it is particularly preferable that the component (a) / component (b) (weight ratio) is 10 / 90 to 50 / 50.

[0018] When the ethylene-based resin (III) is one in which the ultra-high molecular weight component (III) and the low molecular weight component (III) coexist in a specific ratio, the component (III) can be highly dispersed when blended with polyethylene, making it possible to highly modify the mechanical properties of the extrusion molded article without impairing the appearance.

[0019] In order to provide an extrusion molded product having a particularly excellent balance between dispersibility in polyethylene and improved mechanical properties, the ethylene-based resin (C) preferably has (3) Mw / Mn, calculated as linear polyethylene as measured by GPC, of ​​4.0 or more and less than 50, and particularly preferably 4.0 or more and 30 or less.

[0020] In addition, since the components (A) and (B) are different from a simple blend in which each component is independently dispersed, the ethylene-based resin (C) is (4) measured using a differential scanning calorimeter (hereinafter sometimes referred to as DSC) by heating from 0°C to 230°C at a heating rate of 10°C / min (hereinafter sometimes referred to as 1st scan) at a crystal melting peak (hereinafter referred to as Tm 1 It is preferable that the peak intensity distribution is unimodal.

[0021] The ethylene-based resin (iii) constituting the extrusion molded product of the present invention may be any resin as long as it satisfies the above-mentioned characteristics. In particular, it is preferable that the resin is produced using a metallocene-based catalyst, since it is easy to control the molecular weight and molecular weight distribution and to produce an (ultra)high molecular weight resin. In particular, examples of a method for producing the ethylene-based resin (iii) having both components (i) and (ii) include a method using a co-supported catalyst in which two or more types of metallocene complexes are supported on a carrier as the catalyst system, and a method using multi-stage polymerization of two or more stages.

[0022] The polymerization method of the ethylene-based resin (iii) may be, for example, a solution polymerization method, a bulk polymerization method, a gas phase polymerization method, a slurry polymerization method, etc., among which, the slurry polymerization method is preferable since it enables the production of an ethylene-based resin with a regular particle shape. The solvent used in the slurry polymerization method may be any organic solvent that is generally used, for example, benzene, toluene, xylene, pentane, hexane, heptane, etc., and liquefied gases such as isobutane and propane, and olefins such as 1-butene and 1-hexene can also be used as the solvent.

[0023] The production catalyst used to produce the ethylene-based resin (iii) may be any catalyst capable of producing the ethylene-based resin. For example, in the case of multi-stage polymerization, a metallocene catalyst obtained from at least a transition metal compound (A-1), an organically modified clay modified with an aliphatic salt (B), and an organoaluminum compound (C) may be used. For example, in the case of a co-supported catalyst method, a metallocene catalyst obtained from at least a transition metal compound (A-1), a transition metal compound (A-2), an organically modified clay modified with an aliphatic salt (B), and an organoaluminum compound (C) may be used.

[0024] Examples of the transition metal compound (A-1) include transition metal compounds having a (substituted) cyclopentadienyl group and a (substituted) fluorenyl group, transition metal compounds having a (substituted) cyclopentadienyl group and a (substituted) indenyl group, transition metal compounds having a (substituted) indenyl group and a (substituted) fluorenyl group, and the like. In this case, examples of the transition metal include zirconium and hafnium, and among these, zirconium compounds having a (substituted) cyclopentadienyl group and an amino group-substituted fluorenyl group and hafnium compounds having a (substituted) cyclopentadienyl group and an amino group-substituted fluorenyl group are preferred, as they enable efficient production of an ethylene-based resin suitable for an extrusion molded product.

[0025] More specifically, for example, diphenylmethylene(1-indenyl)(9-fluorenyl)zirconium dichloride, diphenylmethylene(1-indenyl)(2,7-di-t-butyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(4-phenyl-1-indenyl)(2,7-di-t-butyl-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2-(dimethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2-(dimethylamino)-9-fluorenyl)zirconium dichloride, )(2-(diethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2-(dibenzylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-bis(dimethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-bis(diethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-bis (dibenzylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(4-(dimethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(4-(diethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(4-(dibenzylamino)-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-9-fluorenyl)zirconium dichloride diphenylmethylene(cyclopentadienyl)(2-(diethylamino)-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(diethylamino)-7-ethyl-9-fluorenyl)zirconium dichloride,Diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-7-ethyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-7-ethyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-7-n-propyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(diethylamino)-7-n-propyl-9-fluorenyl)zirconium dichloride diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-7-n-propyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-7-n-propyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-7-isopropyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(diphenylmethylene)(cyclopentadienyl)(2-(diphenylmethylene)(cyclopentadienyl) diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-7-isopropyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-7-isopropyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-7-n-butyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-7-n-butyl-9-fluorenyl)zirconium dichloride Examples of zirconium compounds include diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-7-t-butyl-9-fluorenyl)zirconium dichloride and diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-7-t-butyl-9-fluorenyl)zirconium dichloride; zirconium compounds in which the dichloro form of these compounds is replaced with a dimethyl form, a diethyl form, a dihydro form, a diphenyl form or a dibenzyl form; and hafnium compounds in which the zirconium of these compounds is replaced with hafnium.

[0026] Examples of the transition metal compound (A-2) include a transition metal compound having a (substituted) cyclopentadienyl group and a (substituted) fluorenyl group, a transition metal compound having a (substituted) cyclopentadienyl group and a (substituted) indenyl group, and a transition metal compound having a (substituted) indenyl group and a (substituted) indenyl group.

[0027] More specifically, dimethylsilanediylbis(cyclopentadienyl)zirconium dichloride, diethylsilanediylbis(cyclopentadienyl)zirconium dichloride, dicyclohexylsilanediylbis(cyclopentadienyl)zirconium dichloride, diphenylsilanediylbis(cyclopentadienyl)zirconium dichloride, dimethylsilanediylbis(methylcyclopentadienyl)zirconium dichloride, diethylsilanediylbis(methylcyclopentadienyl)zirconium dichloride, dicyclohexylsilanediylbis(cyclopentadienyl)zirconium dichloride, Silanediylbis(methylcyclopentadienyl)zirconium dichloride, diphenylsilanediylbis(methylcyclopentadienyl)zirconium dichloride, dimethylsilanediylbis(2,4-dimethylcyclopentadienyl)zirconium dichloride, diethylsilanediylbis(2,4-dimethylcyclopentadienyl)zirconium dichloride, dicyclohexylsilanediylbis(2,4-dimethylcyclopentadienyl)zirconium dichloride, diphenylsilanediylbis(2,4-dimethylcyclopentadienyl)zirconium dichloride silanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, dimethylsilanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, diethylsilanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, dicyclohexylsilanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, diphenylsilanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, dimethylsilanediyl[(cyclopentadienyl)(4,7-dimethylindenyl)]zirconium dichloride silanediyl[(cyclopentadienyl)(4,7-dimethylindenyl)]zirconium dichloride, dicyclohexylsilanediyl[(cyclopentadienyl)(4,7-dimethylindenyl)]zirconium dichloride, diphenylsilanediyl[(cyclopentadienyl)(4,7-dimethylindenyl)]zirconium dichloride, dimethylsilanediyl[(cyclopentadienyl)(2,4,7-trimethylindenyl)]zirconium dichloride, diethylsilanediyl[(cyclopentadienyl)(2,4,7-trimethylindenyl)]zirconium dichloride, dicyclohexylsilanediyl[(cyclopentadienyl)(2,4,7-trimethylindenyl)]zirconium dichloride, diphenylsilanediyl[(cyclopentadienyl)(2,4,7-trimethylindenyl)]zirconium dichloride, bis(indenyl)zirconium dichloride, isopropylidenebis(indenyl)zirconium dichloride, (methyl)(phenyl)methylenebis(indenyl)zirconium dichloride, diphenyl Phenylmethylene bis(indenyl)zirconium dichloride, ethylene bis(indenyl)zirconium dichloride, isopropylidene bis(2-methylindenyl)zirconium dichloride, (methyl)(phenyl)methylene bis(2-methylindenyl)zirconium dichloride, diphenylmethylene bis(2-methylindenyl)zirconium dichloride, ethylene bis(2-methylindenyl)zirconium dichloride, isopropylidene bis(tetrahydroindenyl)zirconium dichloride , (methyl)(phenyl)methylenebis(tetrahydroindenyl)zirconium dichloride, diphenylmethylenebis(tetrahydroindenyl)zirconium dichloride, ethylenebis(tetrahydroindenyl)zirconium dichloride, isopropylidene(cyclopentadienyl)(fluorenyl)zirconium dichloride, (methyl)(phenyl)methylene(cyclopentadienyl)(fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(fluorenyl)zirconium dichloride dichloride, ethylene(cyclopentadienyl)(fluorenyl)zirconium dichloride, isopropylidene(cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride, (methyl)(phenyl)methylene(cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride, ethylene(cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride; zirconium compounds in which the dichloro form of these compounds is replaced with a dimethyl form, a diethyl form, a dihydro form, a diphenyl form, or a dibenzyl form; and hafnium compounds in which the zirconium of these compounds is replaced with hafnium.

[0028] Examples of the organically modified clay (B) modified with an aliphatic salt include N,N-dimethyl-behenylamine hydrochloride, N-methyl-N-ethyl-behenylamine hydrochloride, N-methyl-Nn-propyl-behenylamine hydrochloride, N,N-dioleyl-methylamine hydrochloride, N,N-dimethyl-behenylamine hydrofluoride, N-methyl-N-ethyl-behenylamine hydrofluoride, N-methyl-Nn-propyl-behenylamine hydrofluoride, N,N-dioleyl-methylamine hydrofluoride, N,N-dimethyl-behenyl ... behenylamine hydrobromide, N-methyl-N-ethyl-behenylamine hydrobromide, N-methyl-Nn-propyl-behenylamine hydrobromide, N,N-dioleyl-methylamine hydrobromide, N,N-dimethyl-behenylamine hydroiodide, N-methyl-N-ethyl-behenylamine hydroiodide, N-methyl-Nn-propyl-behenylamine hydroiodide, N,N-dioleyl-methylamine hydroiodide, N,N-dimethyl-behenylamine sulfate, N-methyl-N-ethyl-behenylamine sulfate aliphatic amine salts such as N-methyl-Nn-propyl-behenylamine sulfate and N,N-dioleyl-methylamine sulfate; P,P-dimethyl-behenylphosphine hydrochloride, P,P-diethyl-behenylphosphine hydrochloride, P,P-dipropyl-behenylphosphine hydrochloride, P,P-dimethyl-behenylphosphine hydrofluoride, P,P-diethyl-behenylphosphine hydrofluoride, P,P-dipropyl-behenylphosphine hydrofluoride, P,P-dimethyl-behenylphosphine hydrobromide, P,P- Examples of the clay modified with an aliphatic salt include aliphatic phosphonium salts such as diethyl-behenylphosphine hydrobromide, P,P-dipropyl-behenylphosphine hydrobromide, P,P-dimethyl-behenylphosphine hydroiodide, P,P-diethyl-behenylphosphine hydroiodide, P,P-dipropyl-behenylphosphine hydroiodide, P,P-dimethyl-behenylphosphine sulfate, P,P-diethyl-behenylphosphine sulfate, and P,P-dipropyl-behenylphosphine sulfate.

[0029] The clay compound constituting the organically modified clay (B) may be any compound as long as it belongs to the category of clay compounds. In general, the organically modified clay (B) is formed by stacking many layers called silicate layers, which are composed of a tetrahedral sheet of silica tetrahedrons connected in two dimensions and an octahedral sheet of alumina octahedrons or magnesia octahedrons connected in two dimensions in a 1:1 or 2:1 ratio. The Si in some of the silica tetrahedra is replaced by Al, the Al in the alumina octahedrons by Mg, and the Mg in the magnesia octahedrons by Li, etc., resulting in a lack of positive charges within the layers and the layers as a whole being negatively charged. In order to compensate for this negative charge, Na is introduced between the layers. + Or Ca 2+ As the clay compound, there are natural or synthetic products such as kaolinite, talc, smectite, vermiculite, mica, brittle mica, and malachite, and these can be used, among which smectite is preferred because of its ease of availability and ease of organic modification, and among smectites, hectorite or montmorillonite is even more preferred.

[0030] The organically modified clay (B) can be obtained by introducing the aliphatic salt between the layers of the clay compound to form an ion complex. When preparing the organically modified clay (B), it is preferable to select conditions of a clay compound concentration of 0.1 to 30% by weight and a treatment temperature of 0 to 150°C. The aliphatic salt may be prepared as a solid and dissolved in a solvent for use, or a solution of the aliphatic salt may be prepared by chemical reaction in a solvent and used as is. As for the reaction ratio of the clay compound and the aliphatic salt, it is preferable to use an equivalent or greater amount of aliphatic salt relative to the exchangeable cations of the clay compound. Examples of the treatment solvent that can be used include aliphatic hydrocarbons such as pentane, hexane, and heptane; aromatic hydrocarbons such as benzene and toluene; alcohols such as ethyl alcohol and methyl alcohol; ethers such as ethyl ether and n-butyl ether; halogenated hydrocarbons such as methylene chloride and chloroform; acetone; 1,4-dioxane; tetrahydrofuran; water, and the like. It is preferable to use alcohols or water alone or as one component of the solvent.

[0031] In addition, the particle size of the organically modified clay (B) constituting the production catalyst is not limited, and is preferably 1 to 100 μm, since it is excellent in efficiency during catalyst preparation and efficiency during ethylene-based resin production. There is also no limit to the method of adjusting the particle size, and large particles may be crushed to an appropriate particle size, small particles may be granulated to an appropriate particle size, or crushing and granulation may be combined. In addition, the particle size may be adjusted either on the clay before organic modification or on the organically modified clay after modification.

[0032] As the organoaluminum compound (C), any compound that belongs to the category called an organoaluminum compound can be used, and examples thereof include alkylaluminum such as trimethylaluminum, triethylaluminum, and triisobutylaluminum.

[0033] The proportions of the transition metal compounds (A-1) and (A-2) (hereinafter, the transition metal compounds (A-1) and (A-2) are collectively referred to as component (A)), the organically modified clay (B) (hereinafter, also referred to as component (B)), and the organoaluminum compound (C) (hereinafter, also referred to as component (C)) constituting the production catalyst are not subject to any restrictions as long as they can be used as a production catalyst. In particular, in order to provide a production catalyst capable of efficiently producing the ethylene-based resin (C), the molar ratio per metal atom of component (A) to component (C) is preferably in the range of component (A):component (C)=100:1 to 1:100,000, and more preferably in the range of 1:1 to 1:10,000. Furthermore, the weight ratio of component (A) to component (B) is preferably component (A):component (B)=10:1 to 1:10000, and more preferably in the range of 3:1 to 1:1000.

[0034] Regarding the preparation method of the production catalyst, any method may be used as long as it is possible to prepare a production catalyst containing the (A) component, the (B) component, and the (C) component, and for example, a method of mixing the (A), (B), and (C) components in a solvent inert to the respective components, or using the monomer to be polymerized as a solvent, can be mentioned. In addition, there is no restriction on the order in which these components are reacted, and there is no restriction on the temperature and time of this treatment. In addition, it is also possible to prepare a production catalyst using two or more kinds of each of the (A), (B), and (C) components.

[0035] The polymerization conditions such as polymerization temperature, polymerization time, polymerization pressure, and monomer concentration when producing the ethylene resin (iii) can be arbitrarily selected, and among them, it is preferable to carry out the polymerization at a polymerization temperature of 0 to 100°C, for a polymerization time of 10 seconds to 20 hours, and at a polymerization pressure of normal pressure to 100 MPa. It is also possible to adjust the molecular weight by using hydrogen or the like during the polymerization. The polymerization can be carried out by any method such as a batch method, a semi-continuous method, or a continuous method, and it is also possible to carry out the polymerization in two or more stages by changing the polymerization conditions. The polymer particles obtained after the polymerization is completed can be separated and recovered from the polymerization solvent by a conventionally known method, and dried to obtain the product.

[0036] The polyethylene (iv) constituting the extrusion molded product of the present invention has an MFR of 0.01 to 10 g / 10 min and a density of 930 to 980 kg / m 3 Examples of the polyethylene include those mentioned above, and among them, high density polyethylene is preferable. Examples of such polyethylene include (product name) Nipolon Hard (manufactured by Tosoh Corporation) and (product name) Hi-Zex (manufactured by Prime Polymer Co., Ltd.). Here, the polyethylene having an MFR of less than 0.01 g / 10 min or a density of 980 kg / m 3 On the other hand, if the MFR exceeds 10 g / 10 min or the density is less than 930 g / m 3 If it is less than this, the extrudability and / or mechanical properties will be poor.

[0037] The amount of the ethylene resin (c) contained in the polyethylene composition (e) constituting the extrusion molded product of the present invention may be any amount as long as the extrusion molded product exhibits excellent mechanical properties. In particular, since the balance between the mechanical properties and processability is excellent, the polyethylene composition (e) preferably contains 1 to 100 parts by weight of the ethylene resin (c) per 100 parts by weight of the polyethylene (d), and more preferably 5 to 50 parts by weight.

[0038] The polyethylene composition (e) constituting the extrusion molded article of the present invention may be prepared by any method, and examples of the method include a method in which 1 to 100 parts by weight of an ethylene-based resin (c) is mixed with 100 parts by weight of polyethylene (d), and further, if necessary, additives usually used in polyolefins, such as weather resistance stabilizers, heat resistance stabilizers, antistatic agents, antislip agents, antiblocking agents, antifogging agents, lubricants, pigments, nucleating agents, plasticizers, antioxidants, antioxidants, UV absorbers, neutralizing agents, surfactants, slip agents, and inorganic or organic fillers, and then mixed and kneaded using a kneading machine or the like. The conditions for this process may be any as long as they allow the polyethylene composition (e), and examples of the method include a method in which the ethylene-based resin (c) and polyethylene (d), and optionally other additives, are heated, melted, and kneaded at a temperature in the range of 190°C to 250°C for about 20 to 30 seconds using a single-screw or twin-screw melt kneader or the like, and further cut into pellets to be used as an extrusion molding material.

[0039] The extrusion molded article of the present invention can be obtained by molding the polyethylene composition (e) by an extrusion method. As the extruder, a conventionally known extrusion device can be used, for example, a single screw extruder, a twin screw kneading extruder, a ram extruder, a gear extruder, etc., and the extruder may further have an annular die or a T-die, etc.

[0040] The molding conditions may also be those known in the art. For example, an extruder equipped with a die such as a circular die or a T-die may be used to mold an extrusion molded body at a resin temperature of 160 to 240°C, preferably 190 to 220°C, and a die temperature of 170 to 250°C, preferably 190 to 230°C. Water may be used to cool the extrusion molded body, and an air knife or cooling roll may be used when forming a sheet. During molding, paper or cloth may be fed onto the roll to produce artificial leather, waterproof cloth, and various laminated products. The shape and type of the extrusion molded body at that time are not particularly limited, but may be specifically shaped as a sheet, film, pipe, hose, or the like.

[0041] The extrusion molded product of the present invention is particularly excellent in impact resistance, and has a Charpy impact strength of 30 kJ / m measured at 23° C. 2 More preferably, it is equal to or greater than this.

[0042] The extrusion molded product of the present invention can be used for various products, such as nuts, bolts, joints, films, bottles, gaskets, electric wire coatings, tubes, hoses, pipes, valves, sheets, seals, packing, tanks, rollers, cocks, connectors, housings, boxes, and pallets. Effect of the Invention

[0043] The extrusion moldability and mechanical strength of the molded article can be improved, and it is expected that the molded article will be made thinner and have a longer life, and it is expected to be used in a variety of applications. EXAMPLES

[0044] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples as long as the gist of the present invention is not exceeded.

[0045] Unless otherwise specified, the reagents used were either commercially available or synthesized according to known methods.

[0046] The organically modified clay was pulverized using a jet mill (product name: CO-JET SYSTEM α MARK III, manufactured by Seishin Enterprise Co., Ltd.), and the particle size after pulverization was measured using a Microtrack particle size distribution measuring device (product name: MT3000, manufactured by Nikkiso Co., Ltd.) using ethanol as a dispersant.

[0047] The preparation of the catalyst for production, the production of the ethylene resin, and the purification of the solvent were all carried out under an inert gas atmosphere. The hexane solution (20 wt%) of triisobutylaluminum manufactured by Toso Finechem Co., Ltd. was used.

[0048] Furthermore, various physical properties of the ethylene-based resin and polyethylene were measured by the methods shown below.

[0049] ~Measurement of intrinsic viscosity ([η])~ The measurements were performed using an Ubbelohde viscometer, decahydronaphthalene as a solvent, at 135° C., and an ethylene resin concentration of 0.005 wt %.

[0050] ~Measurement of Mw and Mn~ Measurements were performed using an ultra-high temperature GPC (SSC-7110, manufactured by Senshu Scientific Co., Ltd.) equipped with a column (TSKgel GMHHR-H(S)HT, manufactured by Tosoh Corporation) with 1-chloronaphthalene as the eluent at a column temperature of 210°C, a sample concentration of 0.5 mg / ml, and an injection volume of 0.2 ml. The molecular weight calibration curve was calibrated using a standard polystyrene sample, and Mw and Mn were converted to linear polyethylene.

[0051] ~MFR~ The melt flow rate was measured at a temperature of 190° C. under a load of 2.16 kg in accordance with JIS6922-2:1997.

[0052] ~HLMFR~ The melt flow rate was measured at a temperature of 190° C. and a load of 21.6 kg in accordance with JIS6922-2:1997.

[0053] ~Measurement of thermal melting of ethylene resin~ Using a DSC (manufactured by SII NanoTechnology, Inc., product name: DSC6220), the temperature was raised from 0°C to 230°C at a heating rate of 10°C / min (1st scan), and the crystal melting peak (Tm 1 ), heat of fusion (ΔH 1 ) measurements were carried out.

[0054] Furthermore, various physical properties of the extrusion molded products were measured by the methods shown below.

[0055] ~Tensile properties~ The tensile breaking stress of the extrusion molded test pieces (ASTM-1822L compliant, thickness 0.3 mm) was measured at 25°C and 50 mm / min using a tensile testing machine (Tensilon universal material testing machine RTG-1210, manufactured by A&D Co., Ltd.).

[0056] ~Charpy impact strength~ A universal impact testing machine (Toyo Seiki Seisakusho, ISO-PE-Z43) was used, with a support distance of 62 mm and a pendulum load of 4 J. Extrusion-molded test pieces were used, each with a rectangular shape of 80 mm x 10 mm x 2.5 mm and a single notch with a notch angle of 45° and a notch tip radius of 0.25 mm.

[0057] ~Environmental Stress Crack Resistance Test (ESCR)~ To evaluate the chemical resistance of the molded body, an environmental stress crack resistance test was carried out in accordance with JIS K7108 under the conditions of 50°C using a surfactant (Nonion NS210 (10 wt% aqueous solution) manufactured by Nippon Oil & Fats Co., Ltd.). The test specimens used to evaluate the tensile properties were used.

[0058] ~Skin of the molded body~ The appearance of the surface of the extrusion molded product obtained was evaluated visually. ◯: No gel or the like was observed. ×: Poor flow or gelation occurs.

[0059] ~Abrasion resistance evaluation~ Sand abrasion tests were conducted on polyethylene pipes made by extrusion molding. Sand was dropped continuously from a height of 1m for 5 hours while rotating the pipe at 100 rpm, and the amount of abrasion was measured. The smaller the amount of abrasion, the better the abrasion resistance was evaluated.

[0060] Preparation Example 1 (1) Preparation of organically modified clay 300 ml of industrial alcohol (manufactured by Japan Alcohol Sales Co., Ltd., (trade name) Ekinen F-3) and 300 ml of distilled water were placed in a 1-liter flask, 15.0 g of concentrated hydrochloric acid and 42.4 g (120 mmol) of dimethylbehenylamine (manufactured by Lion Specialty Chemicals, (trade name) Lipomin DM22D) were added, and the mixture was heated to 45°C to disperse 100 g of synthetic hectorite (manufactured by BYK Additives Limited, (trade name) Laponite RDS), and then the mixture was heated to 60°C and stirred for 1 hour while maintaining the temperature. After filtering the slurry, it was washed twice with 600 ml of hot water at 60°C and dried in a dryer at 85°C for 12 hours to obtain 125 g of organically modified clay. This organically modified clay was pulverized in a jet mill to a median diameter of 10 μm.

[0061] (2) Preparation of catalyst suspension for production After replacing the air in a 300 ml flask equipped with a thermometer and reflux condenser with nitrogen, 25.0 g of the organically modified clay obtained in (1) and 108 ml of hexane were added, followed by 0.628 g of diphenylmethylene(cyclopentadienyl)(2-diethylamino-9-fluorenyl)zirconium dichloride and 142 ml of a hexane solution of 20 wt% triisobutylaluminum, and the mixture was stirred at 60°C for 3 hours. After cooling to 45°C, the supernatant was removed and washed twice with 200 ml of hexane, and then 200 ml of hexane was added to obtain a suspension of a catalyst for production (solid weight content: 12.5 wt%).

[0062] Preparation Example 2 (1) Preparation of organically modified clay The same procedure as in Preparation Example 1 was followed.

[0063] (2) Preparation of catalyst suspension for production After replacing the air in a 300 ml flask equipped with a thermometer and a reflux condenser with nitrogen, 25.0 g of the organically modified clay obtained in (1) and 108 ml of hexane were added, followed by 0.669 g of diphenylmethylene(cyclopentadienyl)(2,7-di-t-butyl-9-fluorenyl)zirconium dichloride and 142 ml of a hexane solution of 20 wt% triisobutylaluminum, and the mixture was stirred at 60°C for 3 hours. After cooling to 45°C, the supernatant was removed and washed twice with 200 ml of hexane, and then 200 ml of hexane was added to obtain a suspension of a catalyst for production (solid weight content: 12.5 wt%).

[0064] Manufacturing Example 1 As described below, a bimodal polyethylene ethylene-based resin (III-1) was produced by two-stage polymerization in which the polymerization of component (III-1) was successively carried out after the polymerization of component (III-1). The ethylene-based resin (III-1) had an HLMFR of 2.3 g / 10 min and an [η] of 6.5 dl / g.

[0065] Manufacturing of component (A-1) 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the production catalyst obtained in Preparation Example 1 were added to a 10-liter autoclave, and the temperature was raised to 60°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.80 MPa, and slurry polymerization was carried out for 1 hour. 100 g of ethylene was consumed during the polymerization in terms of polyethylene, and the [η] of component (A-1) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 22 dl / g.

[0066] Manufacture of component (B-1) and ethylene resin (C-1) After polymerizing component (a-1), ethylene was continuously fed so that the ethylene partial pressure was maintained at 0.50MPa at 60°C, and hydrogen was intermittently added so that the hydrogen concentration in the gas phase of the autoclave was 4500ppm, and slurry polymerization was carried out for 9 hours to polymerize component (b-1), thereby producing ethylene-based resin (c-1), which is an ethylene homopolymer. During the polymerization, 900g of ethylene was consumed in terms of polyethylene, and the [η] of component (b-1) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 2.0dl / g.

[0067] Manufacturing Example 2 As described below, a bimodal polyethylene ethylene-based resin (III-2) was produced by two-stage polymerization in which the polymerization of component (III-2) was successively carried out after the polymerization of component (III-2). The ethylene-based resin (III-2) had an HLMFR of 0.08 g / 10 min and an [η] of 7.5 dl / g.

[0068] Manufacturing of component (A-2) In a 10-liter autoclave, 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the production catalyst obtained in Preparation Example 1 were added, and the temperature was raised to 60°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.80 MPa, and slurry polymerization was carried out for 2 hours. During the polymerization, 200 g of ethylene was consumed in terms of polyethylene, and the [η] of component (A-2) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 22 dl / g.

[0069] Manufacture of component (B-2) and ethylene resin (B-2) After polymerizing component (a-2), ethylene was continuously fed so that the ethylene partial pressure was maintained at 0.50MPa at 60°C, and hydrogen was intermittently added so that the hydrogen concentration in the gas phase of the autoclave was 4500ppm, and slurry polymerization was carried out for 8 hours to polymerize component (b-2), thereby producing ethylene-based resin (c-2), which is an ethylene homopolymer. During the polymerization, 800g of ethylene was consumed in terms of polyethylene, and the [η] of component (b-2) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 2.0dl / g.

[0070] Production Example 3 As described below, a bimodal polyethylene ethylene-based resin (III-3) was produced by two-stage polymerization in which the polymerization of component (III-3) was successively carried out after the polymerization of component (III-3). The ethylene-based resin (III-3) had an HLMFR of 0.23 g / 10 min and an [η] of 6.6 dl / g.

[0071] Manufacturing of component (A-3) In a 10-liter autoclave, 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the production catalyst obtained in Preparation Example 2 were added, and the temperature was raised to 70°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.80 MPa, and slurry polymerization was carried out for 2.5 hours. During the polymerization, 500 g of ethylene was consumed in terms of polyethylene, and the [η] of component (A-3) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 10 dl / g.

[0072] Manufacture of component (B-3) and ethylene resin (B-3) After polymerization of component (a-3), ethylene was continuously fed so that the ethylene partial pressure was maintained at 0.87MPa at 60°C, and hydrogen was intermittently added so that the hydrogen concentration in the gas phase of the autoclave was 4500ppm, and slurry polymerization was carried out for 2.5 hours to polymerize component (b-3), thereby producing ethylene-based resin (c-3), which is an ethylene homopolymer. During the polymerization, 500g of ethylene was consumed in terms of polyethylene, and the [η] of component (b-3) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 2.0dl / g.

[0073] Production Example 4 As described below, a bimodal polyethylene ethylene resin (III-4) was produced by two-stage polymerization in which the polymerization of component (III-4) was successively carried out after the polymerization of component (III-4). The ethylene resin (III-4) had an HLMFR of 7.2 g / 10 min and an [η] of 3.2 dl / g.

[0074] Manufacturing of component (A-4) In a 10-liter autoclave, 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the production catalyst obtained in Preparation Example 2 were added, and the temperature was raised to 70°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.80 MPa, and slurry polymerization was carried out for 0.5 hours. 100 g of ethylene was consumed during the polymerization in terms of polyethylene, and the [η] of component (A-4) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 10 dl / g.

[0075] Manufacture of component (B-4) and ethylene resin (B-4) After polymerization of component (a-4), ethylene was continuously fed so that the ethylene partial pressure was maintained at 0.87MPa at 60°C, and hydrogen was intermittently added so that the hydrogen concentration in the gas phase of the autoclave was 4500ppm, and slurry polymerization was carried out for 4.5 hours to polymerize component (b-4), thereby producing ethylene-based resin (c-4), which is an ethylene homopolymer. During the polymerization, 900g of ethylene was consumed in terms of polyethylene, and the [η] of component (b-4) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 2.0dl / g.

[0076] [Table 1]

[0077] Example 1 500 g of the ethylene-based resin (H-1) obtained in Production Example 1, polyethylene (manufactured by Tosoh Corporation, (product name) Nipolon Hard 5110 (MFR = 0.9 g / 10 min, density = 961 kg / m 3 500 g of NH5110 (hereinafter sometimes referred to as NH5110) and 2 g of an antioxidant (BASF, (trade name) Irganox B225) were dry blended, and then melt-kneaded at 220°C, 30 rpm, and a discharge rate of 0.8 kg / h using a twin-screw extruder (Toyo Seiki Seisakusho, (trade name) Labo Plastomill parallel twin-screw extruder 2D25S) to obtain a polyethylene composition (E-1). The HLMFR of the polyethylene composition (E-1) was 5.3 g / 10 min.

[0078] The obtained polyethylene composition (E-1) was dried at 40°C for 8 hours, and then an extruded sheet having a thickness of 0.3 mm was obtained using an extrusion molding machine (manufactured by Plastics Engineering Research Institute Co., Ltd., product name T-die extrusion molding machine) set at a cylinder temperature of 220°C and a T-die temperature of 230°C. Test pieces conforming to ASTM-1822L were cut out from the obtained extruded sheet. In addition, an extruded pipe was obtained using a 50 mm extrusion molding machine (L / D=30, full flight screw) with a circular die set at 200°C, and cut into 500 mm lengths to produce extruded pipes having an outer diameter of 30 mm, an inner diameter of 25 mm, and a length of 500 mm.

[0079] The results of various tests on the obtained extrusion molded product are shown in Table 2. The Charpy impact strength was 39 kJ / m 2 and was excellent in impact resistance, environmental temperature resistance, chemical resistance, and abrasion resistance.

[0080] Example 2 An extrusion molded article was obtained in the same manner as in Example 1, except that 200 g of the ethylene resin (III-2) obtained in Production Example 2 and 800 g of polyethylene (NH5110) were used to obtain a polyethylene composition (III-2).

[0081] The extrusion molded products obtained were evaluated, and the results are shown in Table 2.

[0082] Example 3 An extrusion molded article was obtained in the same manner as in Example 1, except that 200 g of the ethylene resin (III-3) obtained in Production Example 3 and 800 g of polyethylene (NH5110) were used to obtain a polyethylene composition (III-3).

[0083] The extrusion molded products obtained were evaluated, and the results are shown in Table 2.

[0084] Example 4 500 g of the ethylene resin (H-3) obtained in Production Example 3 and polyethylene (manufactured by Tosoh Corporation, (product name) Nipolon Hard 8D01A (MFR = 0.05 g / 10 min, density = 957 kg / m 3 An extrusion molded product was obtained in the same manner as in Example 1, except that 500 g of the polyethylene composition (E-4) was obtained by extruding 500 g of the polyethylene composition (E-4).

[0085] The extrusion molded products obtained were evaluated, and the results are shown in Table 2.

[0086] Example 5 An extrusion molded article was obtained in the same manner as in Example 1, except that 500 g of the ethylene resin (III-4) obtained in Production Example 4 and 500 g of polyethylene (NH8D01A) were used to obtain a polyethylene composition (III-5).

[0087] The extrusion molded products obtained were evaluated, and the results are shown in Table 2.

[0088] Example 6 An extrusion molded article was obtained in the same manner as in Example 1, except that 900 g of the ethylene resin (III-4) obtained in Production Example 4 and 100 g of polyethylene (NH8D01A) were used to obtain a polyethylene composition (III-6).

[0089] The extrusion molded products obtained were evaluated, and the results are shown in Table 2.

[0090] [Table 2]

[0091] Comparative Example 1 An extrusion molded article was obtained in the same manner as in Example 1, except that 1000 g of polyethylene (NH5110) and 2 g of an antioxidant (manufactured by BASF, (product name) Irganox B225) were used to obtain a polyethylene composition (E-7).

[0092] The extrusion molded products obtained were evaluated, and the results are shown in Table 3.

[0093] Comparative Example 2 An extrusion molded article was obtained in the same manner as in Example 1, except that 60 g of ultra-high molecular weight polyethylene (manufactured by Mitsui Chemicals, Inc., product name: Million 030S), 940 g of polyethylene (NH5110), and 2 g of an antioxidant (manufactured by BASF, product name: Irganox B225) were used to obtain a polyethylene composition (E-8).

[0094] The extrusion molded products obtained were evaluated, and the results are shown in Table 3.

[0095] Comparative Example 3 Polyethylene (manufactured by Tosoh Corporation, product name Nipolon Hard 8000A (MFR = 0.35 g / 10 min, density = 957 kg / m 3An extrusion molded product was obtained in the same manner as in Example 1, except that 1,000 g of the NH8D01A (hereinafter sometimes referred to as NH8D01A) and 2 g of an antioxidant (manufactured by BASF, (product name) Irganox B225) were used to obtain a polyethylene composition (E-9).

[0096] The extrusion molded products obtained were evaluated, and the results are shown in Table 3.

[0097] Comparative Example 4 500 g of the ethylene resin (H-1) obtained in Production Example 1 and polyethylene (manufactured by Tosoh Corporation, (product name) Nipolon Hard 2000 (MFR = 15 g / 10 min, density = 960 kg / m 3 500 g of NH2000 was used and extrusion molding was attempted in the same manner as in Example 1, but no molded product was obtained.

[0098] Comparative Example 5 500 g of the ethylene resin (H-1) obtained in Production Example 1 and polyethylene (manufactured by Tosoh Corporation, (product name) Nipolon-Z210K (MFR = 2.0 g / 10 min, density = 910 kg / m 3 ), hereinafter sometimes referred to as HF210K), was used in an amount of 500 g, and an extrusion molded product was obtained in the same manner as in Example 1.

[0099] The extrusion molded products obtained were evaluated, and the results are shown in Table 3.

[0100] [Table 3] [Industrial Applicability]

[0101] The extrusion molded product of the present invention can have improved extrusion moldability and mechanical strength, and is expected to have a thinner wall and a longer life.

Claims

1. (1) An ethylene-based resin having a melt flow rate (HLMFR) of 0.01 to 100 g / 10 min at a temperature of 190° C. and a load of 21.6 kg in accordance with JIS 6922-2:1997 and a bimodal elution curve measured by gel permeation chromatography; and a melt flow rate (MFR) of 0.01 to 10 g / 10 min at a temperature of 190° C. and a load of 2.16 kg in accordance with JIS 6922-2:1997 and a density of 930 to 980 kg / m as measured according to JIS K6922-1 (1997). 3 The extrusion molded article is made of a polyethylene composition comprising a polyethylene of the formula:

2. 2. The extrusion molded article according to claim 1, wherein the ethylene-based resin satisfies the following characteristic (2). (2) The elution curve measured by gel permeation chromatography has two peaks, and when the elution curve is expressed as a differential molecular weight distribution (x-axis: Log [M], y-axis: differential distribution value) and the peak is divided into two normal distributions according to the following formula (i), the following (2-1) to (2-3) are satisfied: f(x)=a×(1 / (2π(σ 2 )) (1/2) ) x 2 ) / (2(s 2 ))) formula (i) (Here, a is the peak intensity, σ is the standard deviation, x is the variable, and μ is the average.) (2-1): The weight average molecular weight, calculated as linear polyethylene, based on the peak on the high molecular weight side is 900,000 to 5,000,000, and the molecular weight distribution, expressed as weight average molecular weight / number average molecular weight, is 2.0 to 5.

0. (2-2): The weight average molecular weight, calculated based on the peak on the low molecular weight side, is 10,000 to 500,000 in terms of linear polyethylene, and the molecular weight distribution is 2.0 to 5.

0. (2-3): The weight ratio of the high molecular weight peak to the weight ratio of the low molecular weight peak is greater than 5 / 95 and smaller than 80 / 20.

3. 3. The extrusion molded article according to claim 1, wherein the ethylene-based resin also satisfies the following characteristic (3). (3) The molecular weight distribution, calculated as standard polyethylene, measured by gel permeation chromatography is 4.0 or more and less than 50.

4. 3. The extrusion molded article according to claim 1, wherein the ethylene resin also satisfies the following characteristic (4). (4): The crystal melting peak (Tm) in the first scan measured using a differential scanning calorimeter by heating from 0° C. to 230° C. at a heating rate of 10° C. / min (1st scan) is single-peaked.

5. Charpy impact strength measured at 23°C is 30 kJ / m 2 3. The extrusion molded article according to claim 1 or 2, characterized in that:

6. 3. The extrusion molded article according to claim 1, wherein the ethylene-based resin is an ethylene homopolymer.

Citation Information

Patent Citations

  • JP1973068853A

  • Thermal transfer type sheet

    JP1989005888A

  • Modifier for polyethylene resin, manufacturing method of polyethylene resin composition using the same and manufacturing method of molded body

    JP2017179304A

  • Ultra high molecular weight polyethylene

    JP2021172716A

  • polyethylene resin composition

    JP4173444B2